Rethinking Family Legitimacy in European Law: Legal Recognition and Protection of Unmarried Cohabitants - Oleh Prostybozhenko; Yunina Maryna; Olena Pushkina; Olha Bondarenko; Myroslava Skrynyk (Syariah: Jurnal Hukum dan Pemikiran, 2026)
The recognition of unmarried cohabitants in European law demonstrates an ongoing transformation of the concept of family within modern legal systems. The comparative analysis shows that France, Sweden, Italy, and England and Wales adopt different regulatory approaches, resulting in varying levels of protection concerning property rights, inheritance, social welfare, and relationship dissolution. These differences indicate that legal protection for cohabitants in Europe remains fragmented and inconsistent. The study also confirms the important role of the European Court of Human Rights in expanding the interpretation of “family life” under Article 8 of the European Convention on Human Rights. Nevertheless, significant gaps remain between symbolic recognition and effective legal protection, particularly regarding financial rights and cross-border legal certainty. The absence of harmonized rules governing transnational cohabitation further increases legal uncertainty within the European legal framework. This article argues that the current fragmented legal structure creates vulnerability for unmarried cohabitants, especially economically dependent partners. Therefore, European legal systems should develop minimum protective standards, strengthen the recognition of cohabitation agreements, and improve supranational coordination to ensure equitable and predictable legal protection for contemporary family relationships.